Execution of Guarantee Confiscation by Islamic Financial Institutions without Litigation Process: A Case Study in Magelang - Miswanto, Agus (Muhammadiyah University Press, 2021)
This study attempts to analyze the execution of guarantee confiscation of objects carried out by the Islamic Financial Institutions (LKS) in Magelang. This study uses a statutory approach (statue approach) which is descriptive qualitative by collecting data using the depth interview method. The results of this study indicate that the Islamic Financial Institutions in Magelang in the process of executing collateral do not use litigation, but non-litigation processes. Non-litigation processes used by Islamic Financial Institutions in Magelang is negotiation (consensus) amicably to execute the guarantee. The main reasons for using non-litigation processes, because it is cheap, simple, does not take time, and is friendly. From the findings of this study, the principle of kinship in negotition is still very important and useful for alternative dispute resolution (ADS)